Identification of Niches for Integration of Brachiaria Grasses in Smallholder Mixed Crop-Livestock Farming Systems in Kenya - Njarui, Donald M.G.; Gichangi, Elias M.; Gatheru, Mwangi; Njunie, Michael N.; Nyambati, Elkana; Ndungu, Keziah W.; Mureithi, Joseph G.; Ghimire, Sita R. (International Livestock Research Institute, 2015)
Inadequate quantity and quality of feed is the major constraint to livestock productivity in Kenya. Low rainfall, lack of adapted forages and poor management of sown forages are major factors that affect feed resources production. In most of the farming systems, forages are relegated to the less fertile and degraded soils resulting into poor growth. As a result the growth is poor resulting in deficient in minerals content, low crude protein (CP) and energy. The situation in exacerbated by climate variability and frequent drought. On the other hand, feed resources derived from crop residues, particularly cereals are of poor quality and not sufficient to meet animal production (Njarui and Mureithi, 2006).